The Role of the Merdeka Curriculum in Building an Innovative Generation in the Digital Era - Dhea Ferliza; Ikma Mustaqimah; Siti Lailatun Niamah (The Future of Education Journal, 2025)
In this study, the author follows a meticulous and comprehensive set of research methods to investigate the implementation of Transformative Learning within the context of the Merdeka Curriculum in the Digital Era. The aim of this research is to evaluate the effectiveness of transformative learning in changing educational approaches, as well as to identify its impacts on students, teachers, and the broader education system. The author begins by conducting an in-depth literature review to understand the conceptual and theoretical foundations of transformative learning and the Merdeka Curriculum. Subsequently, the author will collect data through various observations and document analyses. The collected data will be analyzed qualitatively to answer the research questions. The analysis results will be interpreted to evaluate the impact and effectiveness of transformative learning. The author will draw conclusions based on the research findings and propose recommendations for improving the implementation of transformative learning and policy suggestions. The results of this study will be disseminated through publication in academic journals and shared with education stakeholders to contribute to better responses to the ever-evolving demands of the educational world.